Peaking for the World Para Athletics Championships: Case study of a World Champion female Paralympic shot putter - Garcia-Carrillo, E.; Ramirez-Campillo, R. (Journal of Human Sport & Exercise, 2020)
Tapering is used to maximize performance and reduce fatigue levels before athletic competitions. However, scientific evidence regarding Paralympic athletes is scarce. Moreover, no study has assessed the effects of tapering practices on performance in a world champion female Paralympic shot putter (FPSP). Therefore, the aim of this study was to assess the effects of a short tapering period on the performance of an elite FPSP. A world champion FPSP (sport class F54; age 42.2 y; body mass 74 kg; height 1.67 m) was monitored during both overload (2 weeks) and tapering (2 weeks; training volume and intensity decreased) blocks previous to Dubai 2019 World Para Athletics Championships. The internal training load (ITL) (through session rating of perceived exertion) and self-reported wellbeing (using a questionnaire) were assessed daily. Shot put performance was assessed at the beginning and after tapering. The ITL decreased 37.9% with tapering, shot put performance increased 7.6%, there were no differences between weekly wellness scores. No significant correlations were found between ITL and wellbeing indicators. It was concluded that two weeks of tapering induced a rather large improvement in shot put performance. Surprisingly, self-reported wellbeing did not improve with taper as expected.